Analysis of 120 patients with abdominal stab wound focusing on diagnostic role of fast - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2014)
Objective: The purpose of this study was to evaluate the managemant results of patients with penetrating abdominal injuries. Material and Methods: One hundred twenty (120) patients who were admitted to the Emergency Department of Haydarpasa Numune Training and Research Hospital between December 2003 and December 2010 with abdominal stab wounds were included to retrospective study. The data of all patients regarding age, gender, FAST and CT results, injured organs, surgical procedures, length of hospital stay, follow-up were examined. USG findings were classified as follows: true positive (TP), in cases of positive USG findings, and positive laparotomy; true negative (TN), in cases of negative USG findings, and negative physical examination and follow-up findings; false negative (FN), in cases of negative USG findings, and positive laparotomy; and false positive (FP), in cases of positive USG findings, and negative physical examination and follow-up findings. Abdominopelvic CT extended from the lower chest to the symphysis pubis. CT was performed by administering radiopaque agents via intravenous (i.v.) rectal or oral route. Results: One hundred twenty (120) patients who were admitted to the Emergency Department of Haydarpasa Numune Training and Research Hospital between December 2003 and December 2010 with stab abdominal injuries were hospitalized. According to USG findings, 45.7% were TP, 82.4% were TN, 10.6% were FN, and 34.3% were FP. Thirty-five patients with hemodynamic stability and positive FAST findings and 15 patients with positive hemodynamic stability but negative FAST findings underwent computed tomography. Conclusion: Serial FAST and CT help guide treatment for stable patients with penetrating sharp injuries to the abdomen.
Keywords: Stab wound; FAST; computed tomography; PENETRATING TORSO INJURY; MANAGEMENT GUIDELINES; TRAUMA; SONOGRAPHY; ULTRASONOGRAPHY